“Masagi” Simbolisme Pertahanan Ego Sebagai Ide Penciptaan Karya Seni Lukis Still Life - Anindya, Edgina Zelda; Wahyudi, Nandang Gumelar; Rukmana, Nia Kaniasari (ATRAT: Jurnal Seni Rupa, 2025)
In Sundanese culture, there is a philosphy called masagi which focuses on perfection and integration of life experience, however with shock, anxiety, and trauma, this perfectionis is difficult to achieve. To protect ego from feelings of anxiety and traumatic experience faced by humans, ego defense mechanisms emerged. Thie seven of ego defense mechanisms is a tool for humans to manage their emotions and inner shocks that are felt when triggered by one thing or another. In this thesis, the author aims to represent Sigmund Freud’s five ego defense mechanisms through symbolism of things or objects that close to human daily life as a place to reflect on one’s identity and personality. The creation methods used in this work include data collection, incubation, elimination and verification stages. Each work created contains a mask as an individual’s personal symbol. This painting is presented with a still life painting approach in a realist style using oil paint on canvas.